2018
DOI: 10.1111/coa.13124
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on survival of locoregional nasopharyngeal carcinoma: An analysis of the Surveillance, Epidemiology, and End Results program database, 2004‐2013

Abstract: The survival of older patients with NPC is inferior to that of younger patients. Race/ethnicity, marital status, and stage of disease are important modifiers of risk. Collectively, our results indicate that management of older patients requires optimisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 50 publications
5
21
2
Order By: Relevance
“…Besides, regarding to the age in this study, it was refined into four stages, and the results turned out that patients older than 75 years have a significantly worse prognosis. This is consistent with the research of Huang et al [ 21 ], which showed that senior age is a risk factor for poor prognosis. Further investigations are required with a large number of patients admitted in the study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Besides, regarding to the age in this study, it was refined into four stages, and the results turned out that patients older than 75 years have a significantly worse prognosis. This is consistent with the research of Huang et al [ 21 ], which showed that senior age is a risk factor for poor prognosis. Further investigations are required with a large number of patients admitted in the study.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple masses at the primary site imply that the tumor cells are active and more prone to metastasize, which bring a poor prognosis for patients. Previous studies of patients with NPC in the SEER database showed that the race [17,18], marital status [19], and age [20,21] were associated with the prognosis of the patients. However, this is based on patients who have not had distant metastases.…”
Section: Discussionmentioning
confidence: 98%
“…Marital status has been proposed as an important factor associated with oncological outcomes . Previous reports have suggested that unmarried patients have a worse survival than married patients in the case of various cancers such as head and neck, lung, colorectal, pancreatic, breast, and prostate cancer . Consistent with this finding, a survival advantage was observed among married patients in our study ( P < 0.001).…”
Section: Discussioncontrasting
confidence: 76%
“…Nasopharyngeal carcinoma (NPC) is a malignant head and neck tumor with a distinct racial and geographical distribution that is highly prevalent in Southeast Asia [1][2][3]. Currently, the main treatment for NPC is using radiation therapy or a combination of radiation and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%